NAVIGATING THE FINANCIAL LANDSCAPE: Analyzing Stock Returns in the Face of Inflation, Interest Rates, and Investment Risk - Anhari, Agus (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
The decline in stock price has an impact on reducing the results received by shareholders. The purpose of this study is to determine and analyze how the influence of inflation, interest rates, and investment risk on stock yields, with financial performance as a factor that also plays a role, in companies engaged in the food and beverage sector from 2017 to 2021. This study used a descriptive method that looks for relationships between variables, using existing data. To analyze the data, panel data analysis and Eviews 12 software are used. A total of 54 food and beverage companies were the focus of this study, which were listed on the Indonesia Stock Exchange during the period. Sampling is carried out by selected sample method, by purposive sampling. A total of 11 companies were selected as samples in this study. The test results show that together, i.e. simultaneously, inflation, interest rates, investment risk, and financial performance have a significant impact on the stock yield of these companies.